2000
DOI: 10.1046/j.1365-8711.2000.03030.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen and helium abundances in Galactic H II regions -- II. Abundance gradients

Abstract: The absolute integrated fluxes that we obtained (Paper I) for 34 H ii regions, with Galactocentric distances RG in the 6.6–17.7 kpc range, in the emission lines [O ii] λλ3726 and 3729, [O iii] λλ4363 and 5007, He iλ5876, Hα and Hβ, are analysed to derive the extinctions, the electron densities and temperatures, the ionic abundances O+/H+, O++/H+ and He+/H+ and the O/H abundances. The electron temperature has been derived from the [O iii] λ4363/λ5007 ratio in six H ii regions with RG between 6.6 and 14.8 kpc. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

49
259
5
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 219 publications
(315 citation statements)
references
References 62 publications
49
259
5
2
Order By: Relevance
“…Several elements have been investigated, especially oxygen, sulphur, neon and argon in photoionized nebulae (Maciel & Quireza 1999;Deharveng et al 2000) and iron in open cluster stars and cepheids (Friel 1999;Andrievsky et al 2002aAndrievsky et al , 2002b. In the case of the O/H ratio, recent determinations from HII regions, PN and B stars point to an average gradient in the range −0.04 to −0.07 dex/kpc, taking into account an average uncertainty of 0.02 dex/kpc for most determinations.…”
Section: Introductionmentioning
confidence: 99%
“…Several elements have been investigated, especially oxygen, sulphur, neon and argon in photoionized nebulae (Maciel & Quireza 1999;Deharveng et al 2000) and iron in open cluster stars and cepheids (Friel 1999;Andrievsky et al 2002aAndrievsky et al , 2002b. In the case of the O/H ratio, recent determinations from HII regions, PN and B stars point to an average gradient in the range −0.04 to −0.07 dex/kpc, taking into account an average uncertainty of 0.02 dex/kpc for most determinations.…”
Section: Introductionmentioning
confidence: 99%
“…Let us compare this value with recent determinations by other investigators. Caplan et al (2000) and Deharveng et al (2000) have analysed Galactic H ii regions and have obtained the slope -0.0395 dex/kpc with a central oxygen abundance 12+log(O/H) = 8.82 and 12+log(O/H) = 8.48 at the solar galactocentric distance. Rodríguez (1999) considered seven bright Galactic H ii regions with galactocentric distances in the range 6 -10 kpc and has found that all the H ii regions studied are characterized by similar abundances, 12+log(O/H) ∼ 8.45±0.1.…”
Section: The Oxygen Abundance In the Solar Vicinitymentioning
confidence: 99%
“…The name of H ii region is given in column 1. The galactocentric distance taken from Deharveng et al (2000) is reported in column 2. The original oxygen abundance (O/H)SH from Shaver et al (1983) is listed in column 3.…”
Section: Shaver Et Al's Set Of H II Regionsmentioning
confidence: 99%
See 2 more Smart Citations